PROBLEMATIC SITUATION AS METHOD OF ECOLOGICAL COMPETENCE FORMATION OF SENIOR PRESCHOOL CHILDREN - Horopakha, N. (Педагогічна освіта: Теорія і практика. Психологія. Педагогіка., 2017)
This article determines ecological competence formation of preschool children. The author defines pedagogical conditions that promote effective usage of problematic situations in environmental education of senior preschool children. This environmental education is figured as new model foundation of educational system — education for sustainable development. The author proves that ecological competence formation of preschool children is impossible without a significant increase in the efficiency of developing educational technologies which are used in environmental education. In particular, ecological competence formation of preschool children demands combining traditional educational methods with active education methods that require higher level of the child’s self-cognitive activity. Such an activity can be provided only by certain education; this activity expresses new position in the child’s knowledge — subject position. In this case problem education is really effective. The problematic situations can be effective in ecological thinking formation and ecologically correct behavior of preschool children as they help children to set environmental relationships, learn to analyze various situations of human interaction with nature, to understand behaviour rules in nature. Problematic situations efficiency in environmental education of preschool children depends on the level of theoretical and methodological readiness of the teachers to use in their work problem-based learning; preschool children’s research skills; successful combination of problem situations with traditional methods of children’s acquaintance with nature; game usage in creating problem situations. The author also identifies specific methodological requirements to create a problem-game situation so that preschool children get acquainted with the rules of behavior in nature